Organizing pneumonia and COVID-19 - Tonon, Carolina Rodrigues [UNESP]; Tanni, Suzana Erico [UNESP]; Rocha, Juliana [UNESP]; Godoy, Irma [UNESP]; Polegato, Bertha Furlan [UNESP]; Pereira, Filipe Welson Leal [UNESP]; Martins, Danilo [UNESP]; Prudente, Robson Aparecido [UNESP]; Franco, Estefania Thome [UNESP]; Brizola, Fernando [UNESP]; Baldi, Bruno Guedes; Okoshi, Marina Politi [UNESP] (Elsevier, 2023)
Organizing pneumonia (OP) is an interstitial lung disease, and can be cryptogenic, if no cause is identified, or secondary to several conditions. COVID-19-induced persistent inflammation can be associated with interstitial lung disease. We present a review of literature of OP and COVID-19-induced OP with an illustrative case. A 38-year-old man was admitted with COVID-19 that required mechanical ventilation for 56 days. Initial chest computed tomography (CT) revealed diffuse bilateral ground-glass opacities in the lungs with consolidation areas involving 75 % of the parenchyma. After weaning from MV, the patient still required oxygen supplementation. A new chest CT scan also showed extensive diffuse areas of consolidation and ground-glass opacity. OP was hypothesized and 40 mg/day prednisone initiated and continued for six months with resolution of lung functional and image abnormalities. Organizing pneumonia should be included in the differential diagnosis of COVID-19 patients with respiratory symptoms after partial pulmonary recovery.